2021
DOI: 10.3390/su13041743
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Attitudes for Sustainable Mountain Cheese

Abstract: The shift towards more sustainable consumptions and habits have had tangible impacts on food markets, which have accepted this challenge by offering a variety of certification systems to pull consumers aside. However, food purchasing choices are also guided by ethical, environmental and cultural motivations, functioning as drivers of food acquiring. This study aimed at assessing the influence of consumers’ attitudes in purchasing an Alpine cheese labelled with a food sustainability logo, as the mountain produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 74 publications
(140 reference statements)
2
15
0
Order By: Relevance
“…EmojiGrid scores. The positions of the scores on the EmojiGrid valence (X) and arousal (Y) axis were converted into numerical values (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EmojiGrid scores. The positions of the scores on the EmojiGrid valence (X) and arousal (Y) axis were converted into numerical values (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Brand equity combines perceived quality with factors such as brand loyalty, name awareness, and other associations that the consumer may have with the brand [3]. Obviously, the factors vary with the consumer's experience with the product and aid consumers in selecting prod-Foods 2021, 10, 1345 2 of 13 ucts that fit their attitudes [4,5]. Extrinsic variables may also exert direct effects on taste experiences [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Abundant studies have investigated consumer preferences for organic labels [33][34][35], finding that consumers generally believe that organic food is safer, healthier, and more environmentally friendly [36,37], and they are willing to pay a price premium for organic food [15,30,[38][39][40]. Certain studies compare consumer preferences and their willingness to pay for products with different organic certifications [14,41].…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Research by Sajuàn and Khliji [ 49 ] found that mountain beef is appreciated by a niche of consumers; however, the average consumer is only slightly willing to pay more for mountain products compared to conventional ones. More recently, Nam et al [ 50 ] and Mazzocchi et al [ 51 ] found higher willingness to pay for mountain milk and cheese respectively in consumers with higher awareness of animal welfare and agricultural sustainability issues. These results suggest that only specific clusters of consumers would pay more for this characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in a hypothetical scenario, they tend to underestimate the costs of their choices and/or overestimate their willingness to pay for high quality foods [ 56 , 57 , 58 , 59 ]. As a result, the real market premium price for high-quality mountain dairy products does not always compensate mountain farmers for the low productivity of grassland-based farms [ 51 , 60 ].…”
Section: Introductionmentioning
confidence: 99%